2006
DOI: 10.1002/bit.20854
|View full text |Cite
|
Sign up to set email alerts
|

Thermal inactivation of D‐amino acid oxidase from Trigonopsis variabilis occurs via three parallel paths of irreversible denaturation

Abstract: Trigonopsis variabilis D-amino acid oxidase (TvDAO) is a long-known flavoenzyme whose most important biocatalytic application is currently the industrial production of 7-amino-cephalosporanic acid (7-ACA) from cephalosporin C. Lacking mechanistic foundation, rational stabilization of TvDAO for improved process performance remains a problem. We report on results of thermal denaturation studies at 50 degrees C in which two purified TvDAO forms were compared: the native enzyme, and a site-specifically oxidized pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
40
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 39 publications
4
40
0
1
Order By: Relevance
“…We chose reaction conditions that were known from earlier studies with the resting enzyme to promote fast inactivation of the soluble oxidase due to contact with a gas-liquid interface (I. Dib and B.N., unpublished results 2006;Fernández-Lafuente et al, 1998) and thermal denaturation (at 508C; Dib et al, 2006). Time courses of loss of activity were in all cases reasonably well described by a single-exponential decay in the initial phase of inactivation (!40% residual activity), justifying the use of half-life time as parameter describing the kinetic stability of TvDAO (Fig.…”
Section: Stability Of Cdb Clos N-tvdaomentioning
confidence: 98%
“…We chose reaction conditions that were known from earlier studies with the resting enzyme to promote fast inactivation of the soluble oxidase due to contact with a gas-liquid interface (I. Dib and B.N., unpublished results 2006;Fernández-Lafuente et al, 1998) and thermal denaturation (at 508C; Dib et al, 2006). Time courses of loss of activity were in all cases reasonably well described by a single-exponential decay in the initial phase of inactivation (!40% residual activity), justifying the use of half-life time as parameter describing the kinetic stability of TvDAO (Fig.…”
Section: Stability Of Cdb Clos N-tvdaomentioning
confidence: 98%
“…The chosen buffer conditions were similar to those used before by other groups (Schräder & Andreesen 1993;Fernández-Lafuente et al 1999b;Betancor et al 2003). The evidence from experiments and modelling suggests that the mechanism underlying thermal denaturation of Tv DAO in phosphate buffer is essentially the same as that proposed by Dib et al (2006). However, the relative importance of individual denaturation steps is changed upon replacing the original Tris buffer with phosphate buffer.…”
Section: Glu-amidasementioning
confidence: 82%
“…In the course of these studies it was found that the stability of Tv DAO in Tris buffer Dib et al 2006) is quite different from that in phosphate buffer. To determine the source of this ''medium effect'', we performed a detailed analysis of the thermal inactivation of Tv DAO in 100 mmol L (1 sodium phosphate buffer, pH 8.0.…”
Section: Glu-amidasementioning
confidence: 95%
See 1 more Smart Citation
“…Taking into account that loss of FAD appears to be the preponderant path of inactivation of TvDAO under a wide range of conditions (Betancor et al 2003;Dib and Nidetzky 2008;Dib et al 2006;Pollegioni et al 2004), the ability of RgDAO to bind its cofactor by one order of magnitude more tightly than TvDAO made the enzyme from R. gracilis a promising candidate for development of DAO catalysts showing further enhanced robustness. However, exploitation of the extra stability of RgDAO as compared to TvDAO is hampered by relatively inefficient production of the R. gracilis enzyme in both native (Molla et al 2003) and E. coli (Wang et al 2008) host strains.…”
mentioning
confidence: 99%